3.C. Workshop: COVID-19 – Are students' lives turned upside down? Findings from the C19 ISWS study. (20th October 2021) - ,; ,
Abstract:  : The SARS-CoV-2 outbreak and the corresponding COVID-19 pandemic has had and continues to have a significant impact on the health and wellbeing of the general population globally. University students are in a unique position during the COVID-19 pandemic as they are confronted with substantial changes and restrictions, both at governmental and university-level. Stark changes to lifestyle include changes in social and academic life. In order to understand and investigate the impact of the COVID-19 pandemic on student health and well-being, the COVID-19 International Student Well-Being Study (C19 ISWS) was initiated early on in April 2020. Led by researchers at the University of Antwerp, Belgium, a survey questionnaire and protocol was written. Within a few weeks, researchers from 166 high education institutions in 26 different countries had agreed to run the survey in their respective institutions and data was collected from May- July 2020. Up until now, researchers involved in the C19 ISWS consortia have not met and thus far, only a limited amount of researchers have shared their findings. The European Public Health Conference provides a unique opportunity for researchers across countries to share and discuss key findings of the survey, including important public health messages that can be derived from the results of the survey. Presentations on study results of the C19 ISWS will be given by five presenters. Firstly, Prof. Sarah Van De Velde, principal investigator of the study, will provide an overview of the C19 ISWS study design, measures and procedures. Following this introductory talk, four presenters will provide insight into findings of the study at the international level as well as country-level from different regions with varying circumstances during the pandemic (Greece, Russia and Germany). Presentations will be scheduled for seven minutes with three minutes question, followed by a 10-minute discussion at the end. This will allow the audience time to interact with the findings. This works thus aims to provide an exchange and presentation on international as well as country-level findings of the C19 ISWS. Given the shared interest in student health and wellbeing, the joint workshop will provide a further opportunity for researchers to connect. In summary, the objectives of the workshop are: Share and discuss findings of the COVID-19 International Student Well-Being Study Discuss implications of findings for student population internationally including possible measures of actions at individual, community-and structural level Connect researchers and practitioners interested in student health and well-being across Europe and internationally This workshop is aimed at researchers and practitioners with an interest in student health and wellbeing, particularly students in higher education. If possible, a list of attendees and contact details will be collected with participant's agreement and shared amongst all attendees of the workshop. Key messages: The COVID-19 International Student Well-Being Study (C19 ISWS) investigated the impact of the pandemic on students' health, including students of 166 higher education institutions in 26 countries. Findings at country-and international level will be shared and discussed and implications for student's health and wellbeing will be drawn.